1988
DOI: 10.1023/a:1015988401601
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We have shown that the xanthine oxidase-catalyzed anaerobic reduction of nitrofurazone in the presence of added DNA leads to the formation of covalently bound adducts. Further, by systematically decreasing the pH of the reaction mixture, we have demonstrated that generation of the reactive species is facilitated under mildly acidic conditions. From these observations, we conclude that it is the nitrenium ion formed from nitrofurazone which binds to DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Prokaryotes selected for resistance to nitrofurazone invariably acquire mutations in their type I nitroreductase genes. Following activation, the precise antimicrobial action of these prodrugs is largely unknown, but it is believed to rely on production of toxic intermediate metabolites that ultimately trigger DNA damage and cell death (12, 13). In contrast, nitrofuran reduction in eukaryotic cells is generally mediated by enzymes with a type II activity, leading to nitro anion radical formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prokaryotes selected for resistance to nitrofurazone invariably acquire mutations in their type I nitroreductase genes. Following activation, the precise antimicrobial action of these prodrugs is largely unknown, but it is believed to rely on production of toxic intermediate metabolites that ultimately trigger DNA damage and cell death (12, 13). In contrast, nitrofuran reduction in eukaryotic cells is generally mediated by enzymes with a type II activity, leading to nitro anion radical formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in many cases these are reported to be biologically inactive. Instead, prodrug toxicity is believed to occur via formation of protein and nucleic acid adducts with reactive intermediates such as the hydroxylamine or nitrenium ions (12, 13, 47). Here, we demonstrated that the nitrile product generated from nifurtimox is toxic to bloodstream-form trypanosomes, displaying an IC 50 value comparable with that of the parent compound (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, the nitroso and hydroxylamine intermediates can react with biomolecules to exert toxic and mutagenic effects [15,73]. In addition, there is evidence to suggest that hydroxylamines are converted to reactive nitrenium ions, which can react with DNA [73].…”
Section: Figurementioning
confidence: 99%
“…The new concept involving NOS can, however, provide an explanation for the greater reactivity of nilutamide and other nitroarenes towards biological nucleophiles via NOScatalyzed subsequent production of hydroxylamines [26]. For example, the hydroxylamine can be further oxidized to the nitroso (which is an electrophile) or undergo acetylation to the N-acetoxy derivative, forming a highly reactive nitrenium ion that alkylates proteins or DNA [96].…”
Section: Nilutamidementioning
confidence: 99%